2014
DOI: 10.4103/1008-682x.122195
|View full text |Cite
|
Sign up to set email alerts
|

Second to fourth digit ratio: a predictor of adult lung function

Abstract: Sex and sex hormones play a major role in lung physiology. It has been proposed that the ratio of the second to fourth digits (digit ratio) is correlated with fetal sex hormones. We therefore hypothesized that digit ratio might help predict lung function. We investigated the relationship between digit ratio and pulmonary function test (PFT) findings. A total of 245 South Korean patients (162 male, 83 female) aged from 34 to 90 years who were hospitalized for urological surgery were prospectively enrolled. Befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…The literature search (Fig. 1 ) identified 19 partly dependent articles (Vehmas et al 2006 ; Kornhuber et al 2011 , 2013 ; Manning and Fink 2011 ; Herschl et al 2012 ; Borkowska and Pawlowski 2013 ; Romero-Martínez et al 2013 ; Park et al 2014 ; Hoskin and Ellis 2015 ; Han et al 2016 ; Canan et al 2017 , 2018 ; Lenz et al 2017 , 2018a ; Müller et al 2017 ; Cicek et al 2017 ; Hoskin 2017 ; Hobson 2018 ; Kim et al 2018 ) and 18 independent samples. Two studies (Hoskin and Ellis 2015 ; Hoskin 2017 ) are based on the same collective and, therefore, count as one independent sample in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search (Fig. 1 ) identified 19 partly dependent articles (Vehmas et al 2006 ; Kornhuber et al 2011 , 2013 ; Manning and Fink 2011 ; Herschl et al 2012 ; Borkowska and Pawlowski 2013 ; Romero-Martínez et al 2013 ; Park et al 2014 ; Hoskin and Ellis 2015 ; Han et al 2016 ; Canan et al 2017 , 2018 ; Lenz et al 2017 , 2018a ; Müller et al 2017 ; Cicek et al 2017 ; Hoskin 2017 ; Hobson 2018 ; Kim et al 2018 ) and 18 independent samples. Two studies (Hoskin and Ellis 2015 ; Hoskin 2017 ) are based on the same collective and, therefore, count as one independent sample in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…erişkin bireyler üzerinde yaptıkları çalışmada, erkeklerde parmak oranı ile FEV 1 ve FVC oranları arasında pozitif ilişkili bulunduğunu bildirmiştir. 25 Nobari ve ark. genç futbolcular üzerinde yaptığı çalışmada, 2D:4D oranı, kas gücü ve VO 2 maks'taki değişiklikleri önemli ölçüde öngördüğünü bildirmiştir.…”
Section: Discussionunclassified
“…A separate study of adult male Han reported similar digit ratio values of 0.9478 ± 0.0322 for the right hand 3. Park and coworkers1 postulated that age may have had an effect on digit ratio, but if so, the effect must have been subtle since age was not significantly correlated with digit ratio in males or females in their study. Furthermore, the utility of using digit ratio as a biomarker resides in its relative stability throughout life; admittedly, more attention has been paid to postnatal and pubertal modulations of digit ratio 4.…”
mentioning
confidence: 82%
“…In a recent publication appearing in the Asian Journal of Andrology , a team of researchers investigated the relationship of early hormone exposure to adult lung function. In the publication, ‘Second to fourth digit ratio: a predictor of adult lung function’, Park et al ., 1 described known sexual dimorphisms in lung function and a role for sex hormones in the development and regulation of lung function: the predominantly-male hormone, testosterone, enhances airway inflammation and the predominantly female hormone, estrogen, promotes lung development and protects against inflammation. Increasingly over the last decade and a half, digit ratio (the ratio of the lengths of the index to ring fingers) has served as a convenient biomarker for prenatal steroid exposure, and is thought to depend on exposure to testosterone relative to estrogen during development.…”
mentioning
confidence: 99%
See 1 more Smart Citation